Asuhan Keperawatan Pada Ny. S dengan Gangguan Sistem Pernafasan Asma Bronkhiale di Bangsal Melati RSUD Banyudono - Rachmawati, Rizky Eka; , Kartinah, A.Kep, S.Kep (2013)
Background : Asthma is disease airway intermittent obstructive reversible where trachea and bronchi responds in the hyperactive againts certain stimulu.Asthma manifested by narrowing airway resulting dyspnea caughing and whezzing asthma is the disruption of the uning of the bronchiale which can accurrence of respiratory disorders asthma is an interference bronchial tract characterized by bronchospasm periodic ( contraction spasme in the airway ). Destination : To know nursing care in patients with asthma bronkhiale, includes assessment, intervention, implementation and evalvation of nursing. Methods :The author uses the metizod discripstion while the sample is Mrs. S. This data is obtained by : interview, examanation observation activity, obstain records and diagnostic reports, collaborate with co-workers. Result : after the action of nursing during three days, diagnosis appers that : Ineffective airway clearance associated with increased production of secretions, Activity intolerance associated with weakness and fatique secondary due to in adequate oxygenation and difficulty breathing, Anxiety associated with changes in health status and environmental changes. In the implementation of most of the in accordance with the action plan has been implemented.Patients did not experience shortnees of breath, already anxious and can not perform usual activity. Conclusion :After the action of nursing care 3 x 24 hour start date 29 May 2013 up to 31 May 2013 in patients Mrs. S with Asthma Bronkhiale, the authors obtain real experience of provision of nursing care in these patients, authors can directly the process of assessment, determine nursing diagnoses, planning, implementation, evaluation and documentation, on the apllication of the nursing care Mrs. S with asthma bronchiale is not found a problem nursing who do not or have not been resolved.